2022
DOI: 10.1097/iop.0000000000002267
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients With Thyroid Eye Disease Partially Treated With Teprotumumab

Abstract: Purpose: In response to the coronavirus (COVID-19) pandemic, teprotumumab production was temporarily halted with resources diverted toward vaccine production. Many patients who initiated treatment with teprotumumab for thyroid eye disease were forced to deviate from the standard protocol. This study investigates the response of teprotumumab when patients receive fewer than the standard 8-dose regimen. Methods: This observational cross-sectional cohort study included patients from 15 institutions with active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…Currently available real-world data on the use of teprotumumab in the treatment of TED are limited, but several studies including ≥ 10 patients [ 20 – 29 ] suggest that teprotumumab may be effective in a more diverse disease population than that included in clinical trials. For example, in observational cohort studies of patients with heterogeneous TED ( n = 74 [ 20 ] and 21 [ 21 ]), teprotumumab was associated with proptosis response rates of 71–73%, significantly improving outcomes such as proptosis (change in mm; p < 0.01 vs baseline) regardless of TED activity [ 20 , 21 ] or severity [ 21 ].…”
Section: Therapeutic Efficacy Of Teprotumumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently available real-world data on the use of teprotumumab in the treatment of TED are limited, but several studies including ≥ 10 patients [ 20 – 29 ] suggest that teprotumumab may be effective in a more diverse disease population than that included in clinical trials. For example, in observational cohort studies of patients with heterogeneous TED ( n = 74 [ 20 ] and 21 [ 21 ]), teprotumumab was associated with proptosis response rates of 71–73%, significantly improving outcomes such as proptosis (change in mm; p < 0.01 vs baseline) regardless of TED activity [ 20 , 21 ] or severity [ 21 ].…”
Section: Therapeutic Efficacy Of Teprotumumabmentioning
confidence: 99%
“…Currently available real-world data on the use of teprotumumab in the treatment of TED are limited, but several studies including ≥ 10 patients [ 20 – 29 ] suggest that teprotumumab may be effective in a more diverse disease population than that included in clinical trials. For example, in observational cohort studies of patients with heterogeneous TED ( n = 74 [ 20 ] and 21 [ 21 ]), teprotumumab was associated with proptosis response rates of 71–73%, significantly improving outcomes such as proptosis (change in mm; p < 0.01 vs baseline) regardless of TED activity [ 20 , 21 ] or severity [ 21 ]. A retrospective study specifically in chronic (> 2 years), stable TED showed that teprotumumab was associated with a 90% proptosis response rate, as well as significant improvements in proptosis (mm), CAS and diplopia (all p < 0.05 vs baseline; n = 31), and EOM volume and orbital fat volume (both p < 0.01; n = 15) [ 22 ].…”
Section: Therapeutic Efficacy Of Teprotumumabmentioning
confidence: 99%
“…Across all studies, data on 88 patients who were treated with teprotumumab either beyond disease duration of 9 months and/or with a CAS <4 were identified (Table 1) [11 ▪ ,12–14,15 ▪▪ ,16,18,19 ▪ ]. Some authors sought to report specifically on outcomes in patients with longer duration of disease and/or those with low CAS scores at the time of treatment initiation, while others included patients with both high and low CAS scores and reported outcomes separately for the two groups; in such instances, we included their data only from the low CAS cohorts.…”
Section: Extraction Of Cases and Datamentioning
confidence: 99%
“…In the literature included here, participants with low CAS or longer duration TED were intended to be treated with teprotumumab according to the same protocol as described in the phase 2 and phase 3 clinical trials. Specifically, teprotumumab was administered every 3 weeks for eight total doses, with the initial dose being 10 mg/kg and subsequent doses at 20 mg/kg; in one study [12], participants received a variable number of doses because of drug supply interruption, while in a second study, one participant had received only six of eight planned infusions at the time of publication [16]. As noted below, in the largest study reported, participants must have received at least three doses to be included [15 ▪▪ ].…”
Section: Primary and Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation